2014
DOI: 10.15288/jsad.2014.75.859
|View full text |Cite
|
Sign up to set email alerts
|

Parental Alcohol History Differentially Predicts Offspring Disorders in Distinct Subgroups in Israel

Abstract: ABSTRACT. Objective:The association between alcoholism in parents and related disorders in their offspring is well established in cultures with intermediate/high alcohol consumption, but not in those with low consumption, such as Israel. This study investigated differences in parental transmission of alcohol problems and related psychopathology between immigrants from the former Soviet Union (FSU) to Israel and other Israelis-two Israeli subgroups with differing alcohol consumption behaviors and social norms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In our study, parental substance abuse associated both with violent and non-violent offending among female offspring diagnosed with PD later in life. This finding is consistent with previous studies which have shown that parental substance use has found to associate with children's antisocial PD [37,38] and Borderline PD [35]. In our analyses, child welfare placement in adolescence associated with criminality among women with PD.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, parental substance abuse associated both with violent and non-violent offending among female offspring diagnosed with PD later in life. This finding is consistent with previous studies which have shown that parental substance use has found to associate with children's antisocial PD [37,38] and Borderline PD [35]. In our analyses, child welfare placement in adolescence associated with criminality among women with PD.…”
Section: Discussionsupporting
confidence: 93%
“…Past research has indicated that both sleep difficulties (Gregory and Sadeh, 2012) and a parental history of alcoholism (Zucker, 2006) increase the risk of behavioral problems. Even though several studies reported that children of biological, alcohol-dependent parents (COAs) had more internalizing (Eiden et al, 2009; Hussong et al, 2008b) and externalizing problems than non-COAs (Eiden et al, 2007; Meyers et al, 2014), the factors responsible for these differences remain unclear. These factors may explain why some COAs are particularly at risk for behavioral problems.…”
mentioning
confidence: 99%
“…Since research has shown that sexual assault is most commonly associated with PTSD in women (Kessler et al., 1995), it is possible that other risk factors for PTSD development, such as a FH of alcohol dependence, may increase the risk for developing PTSD to a greater extent or exacerbate the effects of exposure to sexual assaultive trauma in women, which could explain our observed result that increasing FHD of alcohol dependence increased the association with PTSD in female participants with sexual assaultive trauma. Prior studies have shown that children who grow up in a household with at least one parent with alcohol dependence are more likely to experience trauma compared to children with unaffected parents (Dube et al., 2001; Meyers et al., 2014). However, these studies have only examined dichotomous parental alcohol dependence status, whereas FHD measures may be more useful (Cservenka et al., 2015; Pandey et al., 2020; Powers et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study demonstrated that mother's alcohol dependence status was positively associated with offspring PTSD (Bender, Meyers, McCutcheon, & Bucholz, 2016). This may be due to adverse aspects of the home environment, like having an abusive or neglectful parent or relative (Breslau et al, 2013), as previous studies have demonstrated that having parents with alcohol use problems increases risk for exposure to a traumatic event (Breslau et al, 2013;Dube et al, 2001;Meyers et al, 2014). Further, individuals with a FH of alcohol dependence are at risk, not just because of their environment, but also because of their genetic risk for alcohol dependence, which shares a substantial overlap in genetic influences with PTSD.…”
Section: Individuals With a Fh Of Alcohol Dependence Have Been Shownmentioning
confidence: 99%
See 1 more Smart Citation